The interaction of RNA polymerase II from wheat with supercoiled and linear plasmid templates. - Lilley, D M (1979)
Interactions between a plant RNA polymerase II and ColE1 based plasmid DNA templates have been studied. Gel electrophoresis indicates that the enzyme binds to both supercoiled and linear species. Using the totally double stranded pMB9/SmaI fragment it is shown that transcription of completely base paired DNA is ten-fold lower than that of denatured or supercoiled plasmid, and reflects the presence of fewer initiation sites. A small proportion of the transcript remains tightly bound to supercoiled templates. 3' oligodeoxycytidine extensions on pMB9/SmaI serve to promote transcription of the linear double stranded form. Using restriction kinetics it is shown that there is a small enhancement of polymerase binding at the pMB9 tetracycline promoter, but that the selectivity of binding at this locus is lower than for the natural bacterial polymerase.